Youth transitions and job quality: How long should they wait and what difference does the family make? - Marianna Filandri; Tiziana Nazio; Jacqueline O'Reilly (Youth Labor in Transition: Inequalities, Mobility, and Policies in Europe, 2018)
This chapter explores how youth unemployment, discontinuous employment, and working in low-quality jobs affect individuals' subsequent occupational conditions. Using cross-sectional and longitudinal EU-SILC data (2005–2012) for five countries, the chapter distinguishes between different types of good and bad jobs, examining the effect of family background on successful transitions. Findings show that young people from families of higher social class have better chances of making transitions into good-quality jobs than do youth from lower class families. Securing a good entry job is crucial to achieving a successful outcome, whereas experiencing either brief periods of unemployment or employment continuity has limited effects. These mechanisms are evident across all countries considered. The findings reinforce established knowledge on patterns of stratification, evidencing a direct channel of social transmission of inequalities through education and an indirect channel through better labor market entries.
Keywords: 330; job quality; family of origin; school-to-work transitions; early labor careers; unemployment duration